Journal for the Advancement of Developing Economies 2018
DOI: 10.13014/k2nz85vx
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Budget Deficit-Economic Growth Nexus: New Evidence From Ghana

Abstract: In this paper, we combine Autoregressive Distributed Lag (ARDL) approach with trend analysis to assess the relationship between Ghana's budget deficit and economic growth from 2000 to 2015 using quarterly data. The trend analysis reveals that since 2000, years of high budget deficit were usually followed by years of low economic growth and vice versa. This phenomenon was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…They found that government expenditure on transport and communication affects private investment positively in developing countries while social security and welfare expenditure of government hinder investment in both developed and developing countries. Nkrumah et al (2016) conducted a study on the relationship between budget deficit and economic growth of Ghana. Based on their trend analysis as well as econometric models they found negative impacts of budget deficit on economic growth.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…They found that government expenditure on transport and communication affects private investment positively in developing countries while social security and welfare expenditure of government hinder investment in both developed and developing countries. Nkrumah et al (2016) conducted a study on the relationship between budget deficit and economic growth of Ghana. Based on their trend analysis as well as econometric models they found negative impacts of budget deficit on economic growth.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…In the midst of the ongoing controversy regarding the relationship between fiscal deficit and economic growth, we find very little work on Ghana. Only a handful of studies (Larbi, ; Antwi et al ., ; Akosah, ; Nkrumah et al ., ; Kurantin, ) have investigated the subject within a Ghanaian context and most of these studies left a number of issues hanging. For instance, these studies focused only on the direct impact and the long‐run relationship between deficit and economic growth using Johansen cointegration and autoregressive distributed lag (ARDL) models which do not account for threshold effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, the crucial weakness of such panel studies calls for more nuanced and in‐depth individual country‐level studies using rich time series data. In the case of Ghana, however, the relatively scanty studies have focused on examining the long‐run relationship between fiscal deficit and economic growth without systematically analysing and estimating the optimal level of fiscal deficits (see Akosah, ; Nkrumah et al ., ; Kurantin, ). This study thus ascertains the path of optimal deficits for Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Goher et al (2012) include timeseries considering the period 1978-2009, to investigate the influence of fiscal deficit on economic growth in Pakistan, applying regression analysis, the findings showed the adverse impact of fiscal deficit on economic growth. Nkrumah et al (2016), used the Autoregressive Distributed Lag (ARDL) approach with trend analysis to assess the relationship between Ghana"s fiscal deficit and economic growth from 2000 to 2015 with quarterly data. Econometric results showed a significant adverse effect of budget deficits on economic growth.…”
Section: Empirical Literaturementioning
confidence: 99%